Chile : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper analyzes the properties of the fiscal surplus rule, a key pillar of Chile's macroeconomic framework. The findings suggest that the rule is near the volatility-minimizing efficiency frontier. The paper assesses the vulnerability of the Chilean banking system to external and domestic shocks, and examines recent trade performance. The study finds that both exports and imports have been driven predominantly by demand factors. There is also some evidence that trade liberalization has contributed to the recent trade expansion, but exchange rate effects are only found to have a marginal impact.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet